Cost-effectiveness of Family Group Conferencing in child welfare: a controlled study - Sharon Dijkstra; Hanneke E. Creemers; Francisca J. A. van Steensel; Maja Deković; Geert Jan J. M. Stams; Jessica J. Asscher (BMC, 2018)
Abstract Background This study aimed to examine the short- and long term (cost-) effectiveness of Family Group Conferencing (FGC) compared to care as usual (CAU) in terms of improved child safety, empowerment and social support. Methods A subgroup of a larger randomized controlled trial, comprising 69 families in child welfare (experimental group: n = 46; control group: n = 23), was included. Results No additional effects of FGC on child safety, social support and only short-term positive effects on empowerment were found. There were no differences in costs between FGC and CAU. The chance for FGC to be cost-effective was small. For families who refused FGC, the FGC approach was more cost-effective than CAU, whereas it was less cost-effective for families that prepared or completed FGC. Conclusions Overall, FGC is not (cost-)effective in improving child safety, empowerment and social support, but cost-effectiveness varies at different levels of FGC-completion. Trial registration Dutch Trial Register number NTR4320. Registered 17 December 2013.